(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article talks about some aspects of the artistic skills of Dostmuhammad Firoqi, a representative of the literary environment of Kokan, in particular, about the art of union, which is widely used in his poetry. In the article, the art of union and its essence, the factors of the emergence of the art of union, the theoretical basis of the use of the art of union in Uzbek poetry, the use of this art in the poems of some poets, in particular, Dostmuhammad Firoqi the role and essence of ghazals and mukhammas are discussed.